Resiliensi Akademik Siswa Fatherless : Tinjauan Literatur Faktor Risiko dan Faktor Protektif Di Lingkungan Sekolah - Firdausiyyah, Kunti Zakiyyatal (FKIP Universitas Islam Jember, 2025)
Fatherlessness can be defined as the absence of a father's role model and influence on his children within the family. This study was conducted through a literature review, utilizing research data published in online journals. A total of 26 articles were collected in this study, with 19 articles passing the review. The results indicate that students with fatherless children tend to experience personal instability. Fatherlessness can be a factor contributing to decreased academic achievement through decreased resilience. Students with a tendency toward fatherlessness are advised to maximize the role of mothers and other family figures who can fill the void of a father figure within them. They are also advised to teach various problem-solving and self-regulation skills. Schools are advised to pay more attention to the crucial or urgent circumstances of each student.